Análise do Índice de Precipitação Padronizada (SPI) para o Estado de São Paulo Através de Técnicas Estatísticas Multivariadas e sua Relação com o Oceano Atlântico Sul - Almeida, Letícia Punski de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Extreme climate events can be responsible for natural disasters with great impact on the population and the environment. In this work, the behavior of the Standardized Precipitation Index (SPI), calculated from monthly precipitation data, between 1981-2020, in the state of São Paulo, was evaluated, looking for extreme periods and homogeneous regions, using statistical methods Principal Components (PCA), Factor (FA) and Clustering (CA). In addition, the relationship between the climate variability of precipitation in these homogeneous regions and teleconnection patterns in the South Atlantic Ocean (SAO) was investigated through correlations with six indexes (Tropical Southern Atlantic Index - TSA, South Atlantic Subtropical Anticyclone Index). - IASAS, South Atlantic Ocean dipole Index - SAODI, South Atlantic Subtropical Dipole index - SASDI, TSM Index in RG2 - ITSMRG2 and SST Index in regions RG2 and RG3 - ITSMRG2+RG3). With the PCA applied to the SPI-1, the first five PCs were selected for rotation, which together explained 97.96% of the variability of the original data. After the rotation of the axes, the PCA indicated anomalous conditions throughout the state, more intense to the east in 42.05% (PC1) of the data, and to the west in 38.31% (PC2). The CA (Ward and K-means) pointed out two homogeneous groups with spatial behaviors in agreement with the first two modes of the rotated PCA. The correlation between the SPI-1 and the SAO indices presented three values of significant correlations (95%) negative in PC1, indicating that when positive anomalies of SST occur (ITSMRG2+RG3 in February and May and TSA in October) there are dry conditions in the east of the state, and showed two in CP2, one negative, indicating that positive SST anomalies (ITSMRG2 in April) occur with dry conditions in the west, and one positive, in which the negative phase of SASDI (in November) occurs in dry conditions in the west of the state of São Paulo.

Os eventos extremos climáticos podem ser responsáveis por desastres naturais com grande impacto à população e ao meio ambiente. Neste trabalho, foi avaliado o comportamento do Índice de Precipitação Padronizado (Standardized Precipitation Index - SPI), calculado a partir dos dados mensais de precipitação, entre 1981-2020, no estado de São Paulo, buscando períodos extremos e regiões homogêneas, utilizando análises estatísticas de Componentes Principais (ACP), Fatorial (AF) e de Agrupamento (AA). Além disso, investigou-se a relação entre a variabilidade climática da precipitação nestas regiões homogêneas e padrões de teleconexões no Oceano Atlântico Sul (OAS), através de correlações com seis índices (Tropical Southern Atlantic Index - TSA, Índice do Anticiclone Subtropical do Atlântico Sul - IASAS, South Atlantic Ocean dipole Index - SAODI, South Atlantic Subtropical Dipole index - SASDI, Índice de TSM na RG2 - ITSMRG2 e Índice de TSM nas regiões RG2 e RG3 - ITSMRG2+RG3). Com a ACP aplicada ao SPI-1, selecionou-se as cinco primeiras CPs para rotação, que juntas explicaram 97,96% da variabilidade dos dados originais. Após a rotação dos eixos, a ACP indicou condições anômalas em todo o estado, mais intensas a leste em 42,05% (CP1) dos dados, e a oeste em 38,31% (CP2). As AA (Ward e K-means) apontaram dois grupos homogêneos com comportamentos espaciais concordantes com os dois primeiros modos da ACP rotacionada. A correlação entre o SPI-1 e os índices do OAS apresentou três valores de correlações significativas (95%) negativas na CP1, apontando que quando ocorrem anomalias positivas de TSM (ITSMRG2+RG3 em fevereiro e maio e TSA em outubro) há condições seca no leste do estado, e apresentou dois na CP2, um negativo, indicando que anomalias positivas de TSM (ITSMRG2 em abril) ocorrem com condições secas no oeste, e um positivo, em que a fase negativa do SASDI (em novembro) ocorrem condições secas no oeste do estado de São Paulo.
Analysis of the Standardized Precipitation Index (SPI) for the State of São Paulo Through Multivariate Statistical Techniques and Its Relationship with the South Atlantic Ocean
Keywords: Extreme events; Precipitation; SPI; São Paulo; Ocean indices; Eventos extremos; Precipitação; SPI; São Paulo; Índices oceânicos